Response of a Group of Sichuan Snub‐Nosed Monkeys to Commercial Logging in the Qinling Mountains, China - SONGTAO GUO; WEIHONG JI; BAOGUO LI; MING LI (Conservation Biology, 2008)
Habitat destruction is one of the greatest threats to primates worldwide. To understand the impact of forest logging on the habitat use of primates in temperate mixed forest, we compared the range, habitat used, population size, and diet of a troop (ERT) of Sichuan snub‐nosed monkeys ( Rhinopithecus roxellana ) in the Qinling Mountains before (1989), during (1997), and after (2002–2003) commercial logging. Logging significantly changed the composition of the forest and the food supply for the troop. Some areas were heavily logged and formed patches in the forest that lacked canopy cover. The troop moved 7 km away from their original range when logging took place and returned to their original range after logging stopped, but they avoided heavily logged areas that lacked canopy cover. Their movement indicated some degree of site fidelity in this species. Diet and home range changed after logging, but the population size remained stable, which suggests that this species has some ability to adapt to habitat changes. Our results may reflect a natural flexibility in primates to adapt to the changing food resources in temperate areas with marked seasonal variations in food availability and distribution. This flexibility may have contributed to their higher degree of resilience to habitat alterations caused by human activities compared with tropical forest primates that have a more specialized diet. Our findings provide important baseline information that will help decision makers in their efforts to conserve primates, especially in temperate regions, and to sustainably manage primate habitat.